Thin GB14 coatings on implants using HVSFS - Lanzino, Maria Carolina; Le, Long-Quan R. V.; Wilbig, Janka; Rheinheimer, Wolfgang; Seidenstuecker, Michael; Günster, Jens; Killinger, Andreas (Frontiers in Materials, 2024)
Enhancing osseointegration, the process by which medical implants securely bond to bone, is crucial for improving patient outcomes in orthopedics and dental surgery. Calcium alkali orthophosphates, with their superior bioactivity, resorbability, and chemical resemblance to bone minerals, have emerged as promising candidates for implant coatings. These materials offer improved solubility and lower melting points due to the substitution of calcium with potassium and sodium, along with the addition of magnesium oxide. This study investigates GB14 calcium alkali orthophosphate coatings applied via High Velocity Suspension Flame Spraying (HVSFS), a technique that enables precise control over coating properties. A porosity target of >10% was set to promote bone growth, and we achieved porosities up to 13%, ensuring better cell penetration and stability at the implant-bone interface. Coatings were produced using different gas parameters and distances, with their microstructure and phase composition analyzed using scanning electron microscope (SEM), Vickers hardness testing and X-ray diffraction (XRD). Additionally, roughness and porosity were also assessed. Different coating’s microstructures were achieved by varying stand-off distance and gas parameters. Increasing stand-off distance while reducing gas stoichiometry enabled the production of calcium alkali orthophosphate coatings with fewer cracks, higher porosity and a hardness level comparable to that of state-of-the-art tricalcium phosphate (TCP) coatings. The sample with optimized properties in terms of achieved microstructure and topography was selected for in vitro testing using MG63 osteosarcoma cells to evaluate cell proliferation and adhesion. WST (I) assay, LDH assay, and live/dead staining confirmed the biocompatibility of the coatings, highlighting the potential of HVSFS to enhance osseointegration and outperform conventional methods in implantology. No relevant cytotoxicity could be shown and cells show a good proliferation over time. These results highlight thus the potential of HVSFS to produce thin, bioactive and resorbable coatings to enhance osseointegration.